2016
DOI: 10.3906/bot-1404-69
|View full text |Cite
|
Sign up to set email alerts
|

The role of anthropogenic habitats as substitutes for natural habitats:a case study on Epipactis helleborine (L.) Crantz (Orchidaceae, Neottieae).Variations in size and nutrient composition of seeds

Abstract: IntroductionEcological comparisons between urban or industrial environments and natural areas emphasize their differences (Lundholm and Richardson, 2010). Humanmodified ecosystems are considered to be ecologically novel in that climatic conditions, soils, toxins, hydrology, productivity, species composition, and interactions (Pickett et al., 2001) differ from conditions prevailing prior to human alterations (Lundholm and Richardson, 2010). The physical, chemical, and biological properties are generally less fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Forests have not been disturbed as much as open localities and therefore there has been less of a decline in the number of suitable localities for E. helleborine. According to Rewicz et al (2015), there are big differences between natural and anthropogenic populations of E. hellebrine in the amount of seed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forests have not been disturbed as much as open localities and therefore there has been less of a decline in the number of suitable localities for E. helleborine. According to Rewicz et al (2015), there are big differences between natural and anthropogenic populations of E. hellebrine in the amount of seed …”
Section: Discussionmentioning
confidence: 99%
“…It grows in forests, at forest edges and also in anthropogenic habitats such as rural and urban road verges, tracks, parks and lawns (Hollingsworth and Dickson 1997;Stefaniak et al 2011) and flowers mainly from June to September (Rewicz et al 2015). In this study, it is the only representative of a forest species.…”
Section: Methodsmentioning
confidence: 99%
“…Hágsater and Dumont (1996) have suggested that orchids belong to the group between ruderal and stress-tolerant plants. Recent studies of Rewicz et al (2016) Manuscript to be reviewed species. In this particular case, it may be caused by reduction in the vigour of other plants by some management practices.…”
Section: Reproductive Success and Effect Of Autogamy Of E Helleborinmentioning
confidence: 99%
“…Manuscript to be reviewed secondary habitats in Central Europe are Epipactis and Dactylorhiza species (Adamowski, 2004;Adamowski, 2006;Esfeld et al, 2008;Rewicz, Kołodziejek & Jakubska-Busse, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…chemical and biological properties of soils found on anthropogenic landscapes are generally less favorable than those in soil found on natural landscapes [46]. For instance, urban soils are characterized by modified soil organism activity and modified soil temperature regimes, elevated soil reaction (pH), greater nutrient amounts and availability to plants, higher calcium levels, more rocks, greater decomposition rates, less accumulated organic matter, and compacted mixtures of anthropogenic materials compared with local remnants of the natural ecosystems [47].…”
Section: Classification and Characterization Of Landscapes In The Casmentioning
confidence: 99%